2004
DOI: 10.1172/jci200422218
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 reduces radiation-induced epithelial apoptosis through a mechanism involving AKT activation and bax translocation

Abstract: Prostaglandin E 2 (PGE 2 ) synthesis modulates the response to radiation injury in the mouse intestinal epithelium through effects on crypt survival and apoptosis; however, the downstream signaling events have not been elucidated. WT mice receiving 16,16-dimethyl PGE 2 (dmPGE 2 ) had fewer apoptotic cells per crypt than untreated mice. Apoptosis in Bax -/-mice receiving 12 Gy was approximately 50% less than in WT mice, and the ability of dmPGE 2 to attenuate apoptosis was lost in Bax -/-mice. Positional analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…COX‐2, an enzyme that catalyzes the formation of prostaglandins, affects tumor cell proliferation and host immune response and is undetectable in most of the normal tissue. Evidence from clinical and preclinical studies indicates that COX‐2‐derived prostaglandins participate in carcinogenesis, suppression of host immunity, apoptosis inhibition, angiogenesis, and tumor cell invasiveness and metastasis . Our previous studies showed that a high expression of COX‐2 is associated with the recurrence and a poor prognosis of patients with NPC, and COX‐2 may play a critical role in chemotherapeutic resistance in NPC via the inhibition of chemotherapy‐induced senescence via the inactivation of p53 .…”
Section: Discussionmentioning
confidence: 99%
“…COX‐2, an enzyme that catalyzes the formation of prostaglandins, affects tumor cell proliferation and host immune response and is undetectable in most of the normal tissue. Evidence from clinical and preclinical studies indicates that COX‐2‐derived prostaglandins participate in carcinogenesis, suppression of host immunity, apoptosis inhibition, angiogenesis, and tumor cell invasiveness and metastasis . Our previous studies showed that a high expression of COX‐2 is associated with the recurrence and a poor prognosis of patients with NPC, and COX‐2 may play a critical role in chemotherapeutic resistance in NPC via the inhibition of chemotherapy‐induced senescence via the inactivation of p53 .…”
Section: Discussionmentioning
confidence: 99%
“…95,[98][99][100] Expression of COX-2 specifically in IMCs protects mice from tissue damage and mucosal repair caused by irradiation, DSS administration, or biopsy injury. 25,101,102 Expression of COX-2 by IMCs is regulated by cytokines (such as TNF and IL-1), microbial products (such as lipoproteins), and growth factors (such as insulin-like growth factor 2 messenger RNA binding protein 1 [IGF2BP1] and FGF9). [25][26][27]103,104 Interestingly, mesenchymal stem cells in the lamina propria express the highest levels of COX-2 and localize to sites of injury where they reposition themselves to mediate tissue repair via MYD88 signaling.…”
Section: Prostaglandin-endoperoxide Synthase 2 (Ptgs2 or Cyclooxygenamentioning
confidence: 99%
“…Together, they play a vital role in the production of prostaglandins that can have both growth-stimulatory and antiapoptotic effects (25). Ptgs1 and -2 have also been shown to play a significant role in protection of the intestine from both irradiation and DSS-mediated damage (24,26,27), primarily though the production of PGE 2 . Recently PGE 2 was shown to transactivate the canonical Wnt signaling pathway (28).…”
Section: Introductionmentioning
confidence: 99%